The Role of Brand Image and Brand Trust in Influenced Brand Loyalty (Survey of Matahari Department Store Cirebon Reward Card Users) - Muhammad Fikry Januar; Rosena Shintabella; Zulfikar Fauzi; Dede Ibrahim Maulana; Solihin (Journal of Applied Digital Business Management, 2025)
The problems identified in this study are the decreasing number of members using Matahari Reward member cards, as well as a decrease in sales which is suspected to indicate a decrease in customer loyalty to the Matahari Department Store brand in Cirebon. This study aims to examine the effect of brand image and brand trust on brand loyalty using quantitative methods. The population studied was 5,200,000 Matahari reward card users, with a sample of 200 respondents selected using probability sampling techniques, namely simple random sampling. Data analysis was carried out using descriptive and verification analysis. The results of the study indicate that brand image and brand trust have a significant influence on brand loyalty, both partially and simultaneously. This shows that consumers' positive perceptions of brand image and their level of trust in the brand contribute to influencing the level of consumer loyalty to the brand. This study provides an important contribution to the understanding of the factors that influence brand loyalty, especially in the context of Matahari Reward Card users. The implication of this finding is that companies can increase consumer loyalty by strengthening a positive brand image and building strong trust in the brand.